MO575: Possible Benefits of a Low Protein Diet in Older CKD Patients at Risk of Malnutrition: A Pilot Randomized Controlled Trial. (3rd May 2022) - Vettoretti, Simone; Caldiroli, Lara; Armelloni, Silvia; Mattinzoli, Deborah; Ikehata, Masami; Molinari, Paolo; Alfieri, Carlo; Messa, Piergiorgio; Castellano, Giuseppe
Abstract: BACKGROUND AND AIMS: Current guidelines do not clarify whether older patients with advanced chronic kidney disease may benefit of low protein diet if they are at risk of malnutrition. We compared the effects of normo-calorie/normo-protein (NP) and normo-calorie/low protein diet (LP) on nutritional status and metabolic complications related to the progression of kidney damage in these patients. METHOD: This pilot study had an open label randomized-controlled design (ClinicalTrials.gov Id: NCT05015647). Thirty-five patients were treated for six months with two different diets (LP = 17) and (NP = 18). Malnutrition was assessed by Malnutrition Inflammation Score and International Society of Renal Nutrition and Metabolism criteria. Renal function was assessed by creatinine and cystatin C based eGFR. RESULTS: At the end of the study, Malnutrition Inflammation Score was improved in both LP and NP groups (respectively: 3 ± 3 versus 6 ± 1.5, P = 0.020 and 3 ± 2.5 versus 6 ± 2, P = 0.012), and prevalence of protein energy wasting syndrome decreased only in LP. LP group had higher eGFRcys-C (17 ± 6 versus 12 ± 4 mL/min/1.73 m 2 ; P < 0.05), lower serum urea (105 ± 65 versus 138 ± 30 mg/dL; P < 0.05) and lower PTH (68 ± 10 versus 99 ± 61 ng/L; P < 0.05) than NP. Serum and urinary phosphorous did not change while FGF23-intact and FGF23 c-terminal increased in both groups (FGF23-intact in LP: 70[48;98] versus 126[90;410] pg/mL, P < 0.01 and in NP: 86[57;194] versus 143[119;186] pg/mL, P < 0.01; FGF23 c-terminal in LP: 77[30.3;112] versus 111[63;384] RU/mL, P < 0.01 and in NP: 142[56.6;175] versus 157[76.7;281] RU/mL, P < 0.01). CONCLUSION: LP diet has a favorable impact on nutritional status as much as NP diet with possible greater benefits on the progression of kidney disease and some of its metabolic complications.